Membangun Proxy Server Cv Global Max Menggunakan Sistem Operasi Linux Blankon 6.0 Ombilin Sebagai Manajemen Akses Jaringan - Wahyudi, Wahyudi (STKIP PGRI Sumatera Barat, 2014)
The computer network is a collection of computers that are connected to each other and work automatically . It can affect the stability of the internet connection that is the amount of bandwidth used and how effective the network bandwidth can be utilized . Bandwidth is a measure of the amount of information that can flow from one place to another within a certain time. Proxy server allows the administrator to limit bandwidth usage can be used by the user and also limit the bandwidth that can be used by a particular file type . One type of method of managing bandwidth using squid . Squid is a caching application GPL ( GNU Public License ) and an implementation of a proxy server that can store objects in the cache . In testing the download and upload can be seen that the system is able to divide bandwidth fairly to all users . To test the content filtering system using two methods, namely filtering with squid and linux BlankonOmbilin. Then the system is also blocking social media access during business hours so that the learning process can proceed smoothly. Keywords: computer networks , bandwidth , squid , blankon 6.0 ombilin, proxy server